Bayesian inference and maximum entropy methods in science and engineering : 25th International Workshop on Bayesian Inference and Maximum Entropy Methods in Science and Engineering, San Jose, California, 7-12 August 2005 - International Workshop on Bayesian Inference and Maximum Entropy Methods in Science and Engineering (25th : 2005 : San Jose, CA.); Knuth, Kevin H. (Kevin Hunter) (Melville, NY : American Inst. of Physics, 2005)
39